Investigating Intercultural Competence in EFL Teaching: Teacher Perception and Action Used to Promote Intercultural Competence - Yusri, Miftahul; Andriyanti, Erna (Journal of Foreign Language Teaching and Learning, 2000)
Background: Integrating intercultural components in foreign language teaching is essential because of the interrelationship between language and culture and the need to understand native and target cultures. Integrating intercultural competence can be done appropriately if the English teacher applies appropriate teaching patterns or strategies to promote intercultural competence in the English classroom. Thus, after implementing intercultural competence, students can adapt to the global society in the future. Objective: The study focuses on revealing (1) teacher’s perceptions of intercultural competence in EFL teaching and (2) the actions they used in promoting intercultural competence in EFL teaching in some senior high schools in two different cities, Yogyakarta and Palembang. Methods: The research is a descriptive study that investigates EFL teachers’ perceptions and the application of intercultural competence in high school. Findings: (1) Participants thought that intercultural competence was crucical to be taught in EFL teaching and that intercultural components such as attitudes, knowledge and skills must be introduced to students in English classroom. It is reflected in the teaching materials, teachers’ syllabi, and information directly from participants. (2) In achieving the learning goals of promoting intercultural competence, all teachers used some actions including media, small group instructions, collaborative dialog, collaborative grouping, and internet-based intercultural contact. Conclusion: Teachers have positive perceptions of integrating of intercultural competencies practices in EFL teaching. However, teachers also faced some problems in integrating intercultural competence such as time limitations in promoting it in EFL learnig, another issue is related to the recent curriculum and EFL textbook, which does not support intercultural knowledge.